2017
DOI: 10.2967/jnmt.116.184473
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Gastric-Emptying Scintigraphy Guidelines: An Analysis of the Intersocietal Accreditation Commission Database

Abstract: CE credit: For CE credit, you can access the test for this article, as well as additional JNMT CE tests, online at https://www.snmmilearningcenter.org. Complete the test online no later than March 2020. Your online test will be scored immediately. You may make 3 attempts to pass the test and must answer 80% of the questions correctly to receive 1.0 CEH (Continuing Education Hour) credit. SNMMI members will have their CEH credit added to their VOICE transcript automatically; nonmembers will be able to print out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Third, the four-hour gastric emptying scintigraphy performed at our medical center differs with regard to meal content, and consequently reference values, from the consensus recommendation [40]. For future studies, use of the recommended gastric emptying scintigraphy is preferred although recent data described that only 3.1% of laboratories were compliant with the recommended protocol [41]. Fourth, high-resolution antroduodenal manometry did not allow us to reliably assess pyloric pressure and pylorospasm.…”
Section: Discussionmentioning
confidence: 95%
“…Third, the four-hour gastric emptying scintigraphy performed at our medical center differs with regard to meal content, and consequently reference values, from the consensus recommendation [40]. For future studies, use of the recommended gastric emptying scintigraphy is preferred although recent data described that only 3.1% of laboratories were compliant with the recommended protocol [41]. Fourth, high-resolution antroduodenal manometry did not allow us to reliably assess pyloric pressure and pylorospasm.…”
Section: Discussionmentioning
confidence: 95%
“…A potential explanation is that subtle changes in motility may promote SIBO, but be insufficiently abnormal to be captured by GES, especially given the ability of unmeasured variables such as poor patient preparation to confound results. 49 Alternatively, the main problem may be dysmotility of the small intestine, which we did not measure. Mechanisms other than dysmotility may also be important, such as exacerbation of GI mucosal immune abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recently, a follow-up study in the United States (US) showed that 69.3% of protocols were not compliant with the content or preparation of the consensus meal. 16 In Asia, literature review showed that there were 3 different types of test meals reported. In Thailand, Vasavid et al 17 used 100 g steamed rice, a microwaved labelled egg, and 100 mL water.…”
Section: Discussionmentioning
confidence: 99%